Molecular and biochemical characterization of the xlnD-encoded 3-hydroxybenzoate 6-hydroxylase involved in the degradation of 2,5-xylenol via the gentisate pathway in Pseudomonas alcaligenes NCIMB 9867 - Gao, X. (2011)
10.1128/JB.187.22.7696-7702.2005